MEMBANGUN KONSEP DIRI POSITIF PADA ANAK - suhendi suhendi (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
Every parent wants his child to grow and develop into a confident, accomplished, intelligent, and happy. But not all hope is able to run as desired. There are children who can grow into a child as desirable, some are not and appear as a problem child. In the perspective of psychological problem of children arises because the psychological needs that are not met and the effects of negative self-concept. The concept of self-importance in sustaining the growth process of children into a positive person, since the concept of self-giving terms of reference to the situation affecting our arrangement and relationship with others. Self-concept is formed by three main components, namely the interplay of Ideal Self, Self Image, and Self-Esteem. By understanding the function of each of these components we will easily do the formation of a positive self-concept of children. For the sake of a positive development for the child, it is important that children have a positive circle of influence of the environment.